TOM1L Is Involved in a Novel Signaling Pathway Important for the IL-2 Production in Jurkat T Cells Stimulated by CD3/CD28 CoLigation - Ahmed Elmarghani; Hanan Abuabaid; Peter Kjellen (Mediators of Inflammation)
TOM1L (target of Myb-1 Like) was identified as a binding partner for the full length and catalytically-active Lck in a yeast 2-hybrid screening assay. Here we show that in Jurkat T cells stimulated by CD3/CD28 coligation where the expression of TOM1L is reduced by lenti virus mediated-siRNA results in a dramatically lower IL-2 production. The production of IL-2 in siRNA treated cells stimulated with PMA/ionomycin was not affected indicating an involvement of TOM1L in a pathway proximal of TCR and CD28. The coexpression of Fyn with TOM1L increased the level of the phosphorylated form of Fyn indicating that TOM1L has the ability to activate Fyn. The ability of TOM1L to activate Fyn was further shown in a kinase assay using angiotensin II as a substrate. By confocal microscopy, we show that the expression of TOM1L in non-treated HeLa and SK-N-SH cells colocalizes with the mitochondrial membrane but not with lysosomal compartments or the trans-Golgi network. Furthermore, we show that the over-expression of TOM1L in Jurkat cells causes an increase of the STAT3 expression . Based on our results, we here propose that TOM1L is involved in a novel signaling pathway that is important for the IL-2 production in T cells.